Youth, University, and Democracy - Dietze, Gottfried (Johns Hopkins University Press, 2020)
Originally published in 1970. Youth, University, and Democracy examines whether Weber's approach has a greater humanizing value than has been conceded by his opponents and will attempt to demonstrate the humanistic mission of the University and its usefulness for youth and democracy.